2021
DOI: 10.3390/biom11050700
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of Acute and Chronic Wound Healing

Abstract: Skin wounds greatly affect the global healthcare system, creating a substantial burden on the economy and society. Moreover, the situation is exacerbated by low healing rates, which in fact are overestimated in reports. Cutaneous wounds are generally classified into acute and chronic. The immune response plays an important role during acute wound healing. The activation of immune cells and factors initiate the inflammatory process, facilitate wound cleansing and promote subsequent tissue healing. However, dysr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
298
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(377 citation statements)
references
References 176 publications
(259 reference statements)
0
298
0
5
Order By: Relevance
“…However, persistent inflammation led to excessive quantities of pro-inflammatory macrophages, whereas the number of macrophages with anti-inflammatory phenotypes became lower. As a result, the establishment of a highly inflammatory environment with an overabundance of inflammatory mediators promotes the degradation of the extracellular matrix, preventing anastomotic healing [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, persistent inflammation led to excessive quantities of pro-inflammatory macrophages, whereas the number of macrophages with anti-inflammatory phenotypes became lower. As a result, the establishment of a highly inflammatory environment with an overabundance of inflammatory mediators promotes the degradation of the extracellular matrix, preventing anastomotic healing [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the inflammatory phase, a number of immune cells, including tissue resident macrophages, and neutrophils and monocytes recruited to the site of injury from the blood, work with numerous cell types in and surrounding the injured skin to orchestrate the repair process [ 27 , 28 ]. This occurs through a combination of the actions of these cells themselves, their signalling pathways, and through the release of their soluble mediators, such as cytokines, chemokines, growth factors, and metabolites that signal other cells to perform specific tasks, to produce the final newly formed tissue [ 24 ].…”
Section: Overview Of the Repair Of An Acute Woundmentioning
confidence: 99%
“…To accommodate the recruitment of a significant number of monocyte cells from the blood, there is an increase in myeloid lineage committed multipotent progenitors and monocytes in bone marrow that results in a 70% increase in monocytes in circulation on day 2, with their levels returning to steady-state levels after around day 4 [ 30 , 38 ]. These monocytes are classified as either classical/pro-inflammatory monocytes that are CD14 + CD16 − capable of differentiating into pro-inflammatory M1 macrophages or anti-inflammatory monocytes that are CD14 low /CD16 + that give rise to mostly M2 macrophages [ 27 ]. In mouse models of wound repair, circulating monocytes can also be divided into two groups: CX3CR1 low CCR2 + Ly6C + and CX3CR1 high CCR2 − Ly6C − [ 15 ].…”
Section: The Inflammatory Phase Of Wound Healing and Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, high levels of hBD-2 and hBD-3 detected at wound sites promote keratinocyte migration and proliferation, indicating their involvement in the re-epithelialization of the healing epithelium [95,112]. A relatively recent study demonstrated that topical insulin delivery to the wound enhanced the levels of extracellular-signal regulated kinase (ERK) and protein kinase B (Akt) [113].…”
Section: Host Defense Peptides Involved In Proliferative Phase Of Wound Healingmentioning
confidence: 99%